Discrete Developmental Roles for Temperate Cereal Grass VERNALIZATION1/FRUITFULL-Like Genes in Flowering Competency and the Transition to Flowering - Preston, Jill C. (American Society of Plant Biologists, 2008)
Members of the grass subfamily Pooideae are characterized by their adaptation to cool temperate climates. Vernalization is the process whereby flowering is accelerated in response to a prolonged period of cold. Winter cereals are tolerant of low temperatures and flower earlier with vernalization, whereas spring cultivars are intolerant of low temperatures and flower later with vernalization. In the pooid grasses wheat (Triticum monococcum, Triticum aestivum) and barley (Hordeum vulgare), vernalization responsiveness is determined by allelic variation at the VERNALIZATION1 (VRN1) and/or VRN2 loci. To determine whether VRN1, and its paralog FRUITFULL2 (FUL2), are involved in vernalization requirement across Pooideae, we determined expression profiles for multiple cultivars of oat (Avena sativa) and wheat with and without cold treatment. Our results demonstrate significant up-regulation of VRN1 expression in leaves of winter oat and wheat in response to vernalization; no treatment effect was found for spring or facultative growth habit oat and wheat. Similar cold-dependent patterns of leaf expression were found for FUL2 in winter oat, but not winter wheat, suggesting a redundant qualitative role for these genes in the quantitative induction of flowering competency of oat. These and other data support the hypothesis that VRN1 is a common regulator of vernalization responsiveness within the crown pooids. Finally, we found that up-regulation of VRN1 in vegetative meristems of oat was significantly later than in leaves. This suggests distinct and conserved roles for temperate cereal grass VRN1/FUL-like genes, first, in systemic signaling to induce flowering competency, and second, in meristems to activate genes involved in the floral transition.